2016
DOI: 10.1111/myc.12524
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of posaconazole oral suspension or delayed‐released tablet salvage treatment for invasive fungal infection

Abstract: Posaconazole may be useful for salvage treatment (ST) for invasive fungal infections (IFIs). The aim of this study was to evaluate the efficacy of posaconazole ST with either posaconazole oral suspension (SUS) or delayed-released tablet (TAB) in patients with IFI. A retrospective review of patients who received posaconazole ST for IFI at the University of Utah Health Sciences Center between December 2007 and March 2014 was conducted. A total of 14 episodes of posaconazole ST for proven (9 episodes) and probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…This result is consistent with the findings reported by Moton et al . Furthermore, Kim et al . reported similar results including adverse events for POS‐Liq and POS‐Tab.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the findings reported by Moton et al . Furthermore, Kim et al . reported similar results including adverse events for POS‐Liq and POS‐Tab.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our study demonstrates only a small number of adverse drug reactions rated as at least possibly associated with novel posaconazole formulations, which is comparable to other published data (Belling et al, 2017;Jeong et al, 2016;Kim et al, 2016). However, a study by Pham et al reported a relatively high rate of hepatotoxity of >10% of the observed patient population who received posaconazole tablet for prophylaxis and therapy of IFDs (Pham et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, nine cases (31%) of rare proven mucormycosis, fusariosis, and trichosporosis were included in the therapy group, well known for high morbidity, mortality, and treatment costs (Heimann et al, 2019;Menzin et al, 2009;Seidel et al, 2017). Nevertheless, the failure rate as reported by the participating investigators is higher than those in previously reported studies (Jeong et al, 2016;Kim et al, 2016;Yi et al, 2017). The high mortality rate in this patient population underlines the urgent need of appropriate empiric and targeted antifungal therapy with respect to both, clinical outcome and associated costs (Zilberberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Posaconazole is a promising alternative and currently used as a salvage therapy for refractory mucormycosis or as step-down therapy [12,33]. Multiple retrospective studies evaluated the utilization of posaconazole as salvage therapy in patients with refractory mucormycosis or intolerance to amphotericin B and showed a favorable response in around 60% of patients [3436]. A new azole, isavuconazole, is the only approved oral antifungal for the treatment of mucormycosis [33,37].…”
Section: Discussionmentioning
confidence: 99%